Analysis of vapor bubble diameter, departure frequency and dynamics in a single cavity - de Oliveira, Jeferson Diehl; da Silva, Isabela Ignácio [UNESP]; de Andrade, Bruno Alves [UNESP]; Cardoso, Elaine Maria [UNESP] (Elsevier, 2024)
The ongoing quest for methods that enhance the efficiency of heat transfer processes, particularly those involving phase change, underscores the importance of comprehending the dynamics of vapor bubbles during boiling. This study investigates heat transfer mechanisms and the dynamics of vapor bubbles within the nucleate boiling regime. Experimental tests were conducted on a flat copper surface featuring a single cavity, focusing on analyzing vapor bubble growth and departure stages. The working fluid examined was HFE-7100 under saturated conditions. The formation and growth aspects of vapor bubbles, including their diameter (Dd) and departure frequency (f), were investigated through experimental data obtained by two different techniques: by an optical sensor of variable resistance capable of generating an analog signal from a voltage change and by a high-speed camera that captures images immediately after the instant that the bubble detached from the surface. Both techniques provide visual insights into the boiling phenomenon. An escalation in heat flux and, consequently, wall superheat resulted in an increased bubble departure frequency. Furthermore, the optical flow analysis successfully identified velocity and vorticity fields induced by micro convection, the prevailing heat transfer mode in nucleated boiling. A slight horizontal displacement trend over time was observed, which may be caused by the asymmetry in the velocity profile, confirmed by velocity peaks tending toward one direction. Vortex analysis reveals rotational motion concentrated in specific regions, with noticeable deformation near the bottom of the bubble and asymmetric movement contributing to vorticity. These findings provide insights into the vapor bubble dynamics, which is important for understanding the cavity rewetting phenomena.
Keywords: Bubble nucleation; Optical flow analysis; Single cavity